Effect of Nimodipine Treatment on the Clinical Course of Reversible Cerebral Vasoconstriction Syndrome - Cho, Soohyun; Lee, Mi Ji; Chung, Chin-Sang (Frontiers in Neurology, 2019)
Background: In reversible cerebral vasoconstriction syndrome (RCVS), nimodipine is currently used for the treatment, although no evidence is available to support its disease-modifying effect. In this prospective observational study, we investigated whether earlier nimodipine treatment can modify the clinical course of reversible cerebral vasoconstriction syndrome. Methods: We prospectively observed patients with angiogram-proven RCVS within 1 month after onset in the Samsung Medical Center between October 2015 and January 2018. Nimodipine was started in all patients immediately after diagnosis. Time from onset to the first nimodipine treatment was categorized as tertiles. We analyzed Kaplan-Meier curve and Cox proportional hazard model to test if the timing of nimodipine treatment can affect the clinical course of thunderclap headaches (TCHs) defined as the duration from onset to remission of thunderclap headaches. Results: In 82 patients included in this study, 71 (86.6%) patients showed remission of TCHs after starting nimodipine treatment. When categorized into earliest (< 6 days), early (6–13 days), and late (≥ 14 days) treatment groups, earlier treatment was significantly associated with shorter clinical courses (median, 2 days [interquartile range 1–3] vs. 7 days [4–10] vs. 10 days [5–15]; log-rank p < 0.001). Univariable and multivariable Cox regression analyses also demonstrated an independent effect of earlier nimodipine treatment on earlier remission of TCHs (adjusted hazard ratio, 0.75 per 1-day delay in treatment; 95% CI, 0.693–0.802, p < 0.001). Conclusions: The clinical course of RCVS differed according to the timing of nimodipine treatment, suggesting the effect of earlier nimodipine treatment. In addition to preventing TCHs, beneficial effects of earlier nimodipine treatment on the progression of vasoconstriction and development of neurological complications should be investigated in future studies.